Medier og selvstændighed i Grønland - Ravn-Højgaard, Signe (2019)
This article discusses the potential impact of Greenlandic independence on Greenland’s media system and suggests initiatives necessary for maintaining strong Greenlandic media in the future. Using Manuel Puppis' (2009) theory of the characteristics of small media systems, the Greenlandic media system is described. It is shown that it is built with the following aim in mind: the media should support the Greenlandic society by being independent and diverse, strengthening the Greenlandic language, and providing quality journalism that can heighten the public debate. However, as a small media system it is vulnerable to global tendencies where legacy media lose users and advertisers to digital platforms like Facebook and streaming services. The article argues that the vulnerability of the Greenlandic media system could increase if independence leads to a tighter public economy, impeding the media's ability to support Greenlandic society and culture. An interventionist media regulation could, therefore, be a prerequisite for a strong Greenlandic media system that can act as a unifying and nation-building institution.